"Meteor, który na chwilkę na scenie naszej zabłysnął..." Okolicznościowe wiersze, toasty i przemówienia opublikowane w prasie poznańskiej w związku z występami gościnnymi Heleny Modrzejewskiej w latach 1880-1903 - Kurek, Krzysztof (Wydawnictwo Księgarnia Akademicka w Krakowie, 2019)
The paper discusses guest performances of the Polish theatrical actress Helena Modjeska in Poznań in 1880, 1890, 1895, and 1903. Based mainly on contemporary press accounts, the author attempts to recapture a unique atmosphere that accompanied these performances. The Polish audience was enthralled by Modjeska's appearances on the stage of the Polish Theatre in Poznań and many local newspapers published extensive accounts of the events and the actress herself received spontaneuos and warn reception. The first part of the paper presents descriptions of the response and attitudes of theaudiences that brilliantly epitomise the 19th century phenomenon of theatrical stardom. Celebrations accompanying Modjeska's visit to Poznań reverberated far beyond Poznań's theatrical community and the walls of the Polish Theatre where she set the stage on fire with her electrifying personality. Grateful spectators would organise formal receptions in honour of the great actress at the Bazar Hotel or banquet venues of a number of other hotels in the town. Poznań-based press published occasional poems and transcribed acclamatory addresses delivered at these events as well as toasts spoken during formal gatherings. The next section of the paper aims to show several such reports (handpicked from a large number) that are the best evidence of the unprecedented and inimitable atmosphere of those days.
Keywords: historia teatru polskiego; biografia artystyczna Heleny Modrzejewskiej; występy gościnne w teatrze polskim XIX w.; historia Poznania; artistic biography of Helena Modjeska; guest performances in 19th c. Polish theatre